Perivascular adipose tissue modulates the effects of flavonoids on rat aorta rings: Role of superoxide anion and β3 receptors. (June 2022) - Ahmed, Amer; Fusi, Fabio; Valoti, Massimo
Abstract: Several studies demonstrate the beneficial effects of dietary flavonoids on the cardiovascular system. Since perivascular adipose tissue (PVAT) plays an active role in the regulation of vascular tone in both health and diseases, the present study aimed to assess the functional interaction between PVAT and flavonoids in vitro on rat aorta rings. Several flavonoids proved to display both antispasmodic and spasmolytic activities towards noradrenaline-induced contraction of rings deprived of PVAT (-PVAT). However, on PVAT-intact (+PVAT) rings, both actions of some flavonoids were lost and/or much decreased. In rings-PVAT, the superoxide donor pyrogallol mimicked the effect of PVAT, while in rings+PVAT the antioxidant mito-tempol restored both activities of the two most representative flavonoids, namely apigenin and chrysin. The Rho-kinase inhibitor fasudil, or apigenin and chrysin concentration-dependently relaxed the vessel active tone induced by the Rho-kinase activator NaF; the presence of PVAT counteracted apigenin spasmolytic activity, though only in the absence of mito-tempol. Similar results were obtained in rings pre-contracted by phenylephrine. Finally, when β3 receptors were blocked by SR59230A, vasorelaxation caused by both flavonoids was unaffected by PVAT. These data are consistent with the hypothesis that both noradrenaline and apigenin activated adipocyte β3 receptors with the ensuing release of mitochondrial superoxide anion, which once diffused toward myocytes, counteracted flavonoid vasorelaxant activity. This phenomenon might limit the beneficial health effects of dietary flavonoids in patients affected by either obesity and/or other pathological conditions characterized by sympathetic nerve overactivity. Graphical Abstract: ga1